Δ9‐Tetrahydrocannabinol promotes functional remyelination in the mouse brain. (2nd August 2021) - Aguado, Tania; Huerga‐Gómez, Alba; Sánchez‐de la Torre, Aníbal; Resel, Eva; Chara, Juan Carlos; Matute, Carlos; Mato, Susana; Galve‐Roperh, Ismael; Guzman, Manuel; Palazuelos, Javier
Abstract : Background and purpose: Research on demyelinating disorders aims to find novel molecules that are able to induce oligodendrocyte precursor cell differentiation to promote central nervous system remyelination and functional recovery. Δ 9 ‐Tetrahydrocannabinol (THC), the most prominent active constituent of the hemp plant Cannabis sativa, confers neuroprotection in animal models of demyelination. However, the possible effect of THC on myelin repair has never been studied. Experimental approach: By using oligodendroglia‐specific reporter mouse lines in combination with two models of toxin‐induced demyelination, we analysed the effect of THC on the processes of oligodendrocyte regeneration and functional remyelination. Key results: We show that THC administration enhanced oligodendrocyte regeneration, white matter remyelination and motor function recovery. THC also promoted axonal remyelination in organotypic cerebellar cultures. THC remyelinating action relied on the induction of oligodendrocyte precursor differentiation upon cell cycle exit and via CB1 cannabinoid receptor activation. Conclusions and implications: Overall, our study identifies THC administration as a promising pharmacological strategy aimed to promote functional CNS remyelination in demyelinating disorders.